Mapping of Diarrhea in Toddlers with Open Defecation Free (ODF) Status in Tuban Regency - Izza Mahendra; Khuliyah Candraning Diyanah; Moch. Irfan Hadi; Sigit Ari Saputro; Syahrul Afifa Ratna Sari (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: The Tuban Regency Health Profile in 2019 stated that the villages with ODF status had reached 64 villages (19.5%) out of 328 total villages, while the villages reported having implemented Community-Based Total Sanitation (CBTS) have reached 100%. The low ODF status achieved indicates that most people still defecate openly, which will increase health risks due to environmental pollution. This study aimed to determine the distribution map of diarrhea in toddlers in each district of Tuban Regency in 2019. Methods: This study was an observational research type supported by mapping through an application with a cross-sectional research design. This study was all districts in Tuban Regency. Data were obtained from secondary data, which were the Tuban Regency Health Profile in 2019. Results and Discussion: The percentage of latrine ownership was 71.15%, the open defecation was 70%, the percentage of children under five was not more than 14.69%, and cases of diarrhea among toddlers were relatively diverse in each district with the lowest number of cases was 0, and the highest number of cases was 841. Conclusion: Diarrhea in toddlers was commonly distributed in the Eastern and Southeastern Tuban Regency, directly adjacent to the Bengawan Solo River. There was a strong possibility that the occurrence of diarrhea was related to the water quality of Bengawan Solo River that was consumed for daily household activities.